ANALISIS PERKEMBANGAN KOGNITIF ANAK USIA 4-5 TAHUN MELALUI BERMAIN LOMPAT ANGKA DI RA AZZAHRA WALANTAKA - kholdun, ibnu (Didaktis: Jurnal Pendidikan dan Ilmu Pengetahuan, 2025)
Low understanding of students' cognitive abilities so that it has an impact on the learning outcomes obtained. This study aims to determine the process of teachers teaching numbers to children using number jumping games in developing cognitive abilities about recognizing symbols of numbers 1-10. Qualitative research method descriptive approach about the use of number jumping games used in kindergarten(RA) Azzahra Walantaka using data collection techniques observation, interviews and documentation. The results of research on the use of number jumping games can make it easier for teachers to introduce number symbols 1-10 and can develop children's cognitive abilities. Indicators developed in the number jumping game are students recognize numbers both orally and in writing, students are able to mention the sequence of numbers 1-10, students are able to make a sequence of numbers 1-10 by jumping numbers and students can understand the concept of 1 by 1 correspondence, namely the word one represents one object. The indicator was chosen because it adapts to the symbolic thinking development stage of children aged 4-5, namely recognizing numbers 1-10. In this study it can be concluded that children's cognitive will develop optimally by using number jumping games that are used continuously and teachers provide support and guidance to students.